Participatory analysis of vulnerability and adaptation to climate change: a methodological guide for working with rural communities. ICRAF Occasional Paper No. 19 - Boureima, Moussa; Abasse, Tougiani A.; Sotelo Montes, Carmen; Weber, John C.; Katkore B; Mounkoro, Bayo; Dakouo, Joseph-Marie; Samaké, Ouodiouma B.; Sigué, Hamadé; Bationo, B. André; Diallo, Boukary O. (World Agroforestry Centre, 2013)
This methodological guide was designed to help researchers and development workers to conduct a participatory analysis of vulnerability and adaptation to climate change (PAVACC) with rural communities, and to develop action plans that reflect the concerns of the rural communities. The approach helps rural communities to assess their vulnerability to climate change, and to identify and plan appropriate activities to reduce their vulnerability. In addition, it helps them to organize and analyze information about the vulnerability and resilience of their community, households and individuals, and to use local knowledge about coping strategies to help them adapt to climate change.